Pendidikan Islam Dalam Perspektif Filsafat Idealisme - Yanuarti, Eka (BELAJEA: Jurnal Pendidikan Islam, 2016)
Idealism is a flow of philosophy that emphasizes the importance of excellence thoughts (mind), soul or spirit instead of the things that are related to immaterial or material. The nature of a human is the soul or the spirit, called "mind". Mind is an entity that is aware of its state, and playing a role as stimulant and stimuli all the human behavior. The role of philosophy in education is to provide a reference in the philosophy of education in order to create an ideal education expected by a society or a nation. Throughout history, the philosophy of idealism is also related to religion, because they both focus on the spiritual aspect. Thus the study of the flow of philosophical idealism towards Islamic education includes issue objectives of Islamic education, Islamic education curriculum, the teaching methods of Islamic education, the learning mateial of Islamic education, learnersâ position in the Islamic education and the role of educators in Islamic education Keywords: Islamic Education, Philosophy and Idealism